A novel motion platform system for testing prosthetic knees. (November 2019) - Xu, Lei; Wang, Dai-Hua; Fu, Qiang; Yuan, Gang; Bai, Xian-Xu
Highlights: A stochastic dynamic process is imitated by the proposed motion platform system. The workload for the gait data measurement is lessened. The thigh motion of a healthy un-amputated individual is imitated in real time. Abstract: The principle of a novel motion platform system (NMPS) for testing prosthetic knees (PKs) is proposed to imitate the stochastic dynamic processes. The NMPS is realized by commanding a thigh simulator to imitate thigh motions of a tester in real time. The NMPS includes a motion platform, a bio-guided unit, a posture sensing unit, and a control and data collection unit. An indirect approach to obtain the vertical motion of the tester's hip joint is proposed and experimentally validated. The prototype of the NMPS is fabricated. The prototype's ability to imitate the tester's thigh motions is experimentally tested at an accelerated/decelerated walking speed. Correspondingly, the swing angle of the developed four-bar linkage prosthetic knee based on magnetorheological effect (FLPKME) is experimentally tested and analyzed. The experimental results indicate that the developed NMPS can accurately imitate the amplitudes and speeds changing in the stochastic dynamic processes of the healthy un-amputated individual's thigh.